MANAJEMEN PASIEN DENGAN KASUS KEGAWATDARURATAN BEDAH MULUT DALAM MASA PANDEMI COVID-19 - Carolina Stevanie Gunawan (Universitas Baiturrahmah, 2021)
Introduction: During the COVID-19 pandemic, oral surgery services were prioritized for emergency cases such as malignancy, head and neck infection, and open or comminuted fracture. COVID-19 that spread by droplets need specific handling considering the work area of an oral surgeon is around the oral cavity and often has close contact with patients. Review: It is important to understand more about COVID-19. In emergency cases that need to be treated immediately, the management to prevent transmission by doing pre-operative, operative, and postoperative procedures will help oral surgery services can be done without the risk of transmission between dentist, patient, and paramedics. Conclusion: Management of emergency cases in oral surgery during pandemic COVID-19 can still be done, if everyone performs proper preventive procedures, not only the dentist but also the patient and paramedics. Conducting telescreens before the visit, early assessment of the patient, preoperative and operative procedures, management of medical waste, and also disinfection of the working area will help to avoid the transmission of COVID-19.